When firms learn from prior acquisition experience - Kalin D. Kolev; Jerayr Haleblian (Journal of Organization Design, 2018)
Acquisition experience is commonly viewed as an important determinant of subsequent acquisition success. Yet, empirical evidence suggests that acquisition experience may not be positively associated with acquisition performance and could even hurt performance. In this article, we highlight specific practices that facilitate and impede learning from acquisitions and draw implications for managers. In particular, we suggest that managers (1) expand time between acquisitions, (2) implement strong governance mechanisms and top management team diversity, (3) use similar-context experience, (4) avoid herding behavior in acquisitions, and (5) minimize blind reliance on financial advisors to effectively transfer prior acquisition experience into acquisition success.
Keywords: 650; Acquisition experience; Acquisition performance; Acquisition transfer